Localization of mitochondria in living cells with rhodamine 123. - Johnson, L V (1980)
The laser dye rhodamine 123 is shown to be a specific probe for the localization of mitochondria in living cells. By virtue of its selectivity for mitochondria and its fluorescent properties, the detectability of mitochondria stained with rhodamine 123 is significantly improved over that provided by conventional light microscopic techniques. With the use of rhodamine 123, it is possible to detect alterations in mitochondrial distribution following transformation by Rous sarcoma virus and changes in the shape and organization of mitochondria induced by colchicine treatment.